Moving in Sync: Hourly Physical Activity and Sedentary Behavior are Synchronized in Couples. Issue 1 (29th May 2019) - Pauly, Theresa; Keller, Jan; Knoll, Nina; Michalowski, Victoria I; Hohl, Diana Hilda; Ashe, Maureen C; Gerstorf, Denis; Madden, Kenneth M; Hoppmann, Christiane A
Abstract: Background: Overall time spent in moderate-to-vigorous intensity physical activity (MVPA) and sedentary behavior are both correlated in couples. Knowledge about the nature and psychosocial correlates of such dyadic covariation could inform important avenues for physical activity promotion. Purpose: The present study investigates hour-by-hour covariation between partners (i.e., synchrony) in MVPA and sedentary behavior as partners engage in their daily lives and links it with person-level MVPA/sedentary behavior, temporal characteristics, and relationship variables. Methods: We used 7-day accelerometer data from two couple studies (Study 1, n = 306 couples, aged 18–80 years; Study 2, n = 108 couples, aged 60–87 years) to estimate dyadic covariation in hourly MVPA and sedentary behavior between partners. Data were analyzed using coordinated multilevel modeling. Results: In both studies, hourly MVPA and sedentary behavior exhibited similarly sized dyadic covariation between partners in the low-to-medium range of effects. Higher MVPA synchrony between partners was linked with higher individual weekly MVPA and higher individual weekly sedentary levels, whereas higher sedentary synchrony between partners was associated with higher individual weekly MVPA but lower individual weekly sedentary levels. MVPA and sedentary synchrony were higher in the morning and evening, more pronounced on weekends, and associated with more time spent together, longer relationship duration, and time-varying perceptions of higher partner closeness. Conclusions: This study demonstrates that MVPA and sedentary behaviors do not occur in a social vacuum. Instead, they are linked with close others such as partners. Thus, capitalizing on social partners may increase the effectiveness of individual-level physical activity interventions. Abstract : Partners tend to mirror each other's active and sitting times (physical activity synchrony), which was associated with greater overall activity levels and positive relationship functioning.